A Novel Study on Present Situation of Infrastructure of Water, Sanitation and Hygiene of Rural People in Bangladesh - Md. Samiul Arefin; Md Ashikur Rahman Talukder; Shoma Hore; Ripon Hore (Western European Studies, 2023)
The study focuses a strong emphasis on how water, sanitation, and hygiene are connected to human lifestyle. In particular, the village of Bordoil Uttarpara in Durgapur North Union's Adarsha Sadar Upazila, Comilla, is discussed in relation to sanitary conditions in Bangladesh. While many drinking water sources now have better infrastructure, the vast majority have not yet been examined for toxins and pathogens. The state of sanitation is good, with all homes using upgraded latrines in line with the general trend. Personal restrooms are widely used, and after two years, proper toilet care has improved. Due to awareness of COVID-19, improved practices and more access to hand washing have been seen. As inappropriate trash disposal is frequent, waste management needs to be improved. Despite the lack of widespread awareness initiatives, household heads are crucial to the promotion of hygiene. The analysis highlights accomplishments and opportunities for improvement in water, sanitation, and hygiene.
Keywords: focuses; emphasis; sanitation